Software Bug Prioritization in Beta Testing Using Machine Learning Techniques - Anum Waqar (Universitas Pendidikan Indonesia, 2020)
Testing in Software Development Life Cycle is one of the most crucial activities. Bug prioritization has been a manual process for long. Our paper provides a methodology for ease of bug prioritization in beta testing phase. In the methodology, data from various bug reports is supplied into a model and, through machine learning, the model outputs fairly accurate bug priority based on historical data.